Empowering Caregivers To Improve Quality Of Life Of Elderly In A Social Institution In Lampung Province, Indonesia - Irianto, Gunawan; Hussain Habil, Mohamad; Hashim, Farida (Journal of World Science, 2022)
Introduction: Elderly Quality of life is a crucial issue for the aging population in developing countries like Indonesia. Studies found that institutionalized elderly have a lower quality of life than in the community. The caregiver’s role in the social institution could be important as social support to enhance the quality of life of the elderly. This study is to empower the caregivers to improve the quality of life of the elderly in a social institution. Methode: A mixed methods exploratory sequential design was used in this study.The WHO-QOL Old questionnaire was used to examine the quality of life and Duke Social Support for social support. Sample for qualitative were seven participants who had experiences that could be explored in detail about their living in a social institution, and 72 participants for quantitative measures Result: The qualitative findings found four main themes that related to elderly experience living in social institutions, support from caregivers, and facility theme was strongly discussed. As for quantitative findings, after the four-month intervention, the score of elderly quality of life before intervention was 45,97 and after intervention 51,54 (p value>0,00), it means empowerment of caregivers significantly improves the quality of life in a social institution. Conclusion: The empowerment of caregivers as social support for the elderly in social institutions has been proven to improve the quality of life of the elderly in social institutions. However, recommendations are suggested including monitoring systems and policy from the management of social institutions need to maintain sustainability programs.